PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SURYA TOTO INDONESIA TBK TANGERANG SELATAN - Renanda Galuh Vitaloka; Suprapto (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of Safety and Health on Employee Performance at PT Surya Toto Indonesia Tbk, South Tangerang both partially and simultaneously. The type of research used is quantitative explanatory research. The data processed is the result of distributing questionnaires to employees of PT Surya Toto Indonesia Tbk, South Tangerang. The data analysis technique used in this study is multiple linear regression. To explain the description of research related to the hypothesis using analysis: Validity Test, Reliability Test, t Test (Partial). Based on the results of data analysis for the t test significance test shows that the variables of Occupational Safety (X1) and Occupational Health (X2) partially have a negative effect on Employee Performance at PT Surya Toto Indonesia Tbk South Tangerang.